2017
DOI: 10.1016/j.ijrobp.2016.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Subtype in Core Lung Biopsies of Early-Stage Lung Adenocarcinoma is a Prognostic Factor for Treatment Response and Failure Patterns After Stereotactic Body Radiation Therapy

Abstract: Purpose Stereotactic body radiation therapy (SBRT) has emerged as an effective treatment for early-stage lung cancer. Histologic subtyping in surgically resected lung adenocarcinomas is recognized as a prognostic factor, with the presence of solid or micropapillary patterns predicting poor outcomes. Herein, we describe outcomes following SBRT for early-stage lung adenocarcinoma by histologic subtype. Materials and Methods We identified 119 consecutive patients (124 lesions) with stage I-IIA lung adenocarcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…Similar results have recently been reported after stereotactic body radiation therapy in the setting of MIP and SOL subtypes. (25) This work may be used to improve patient selection and stratification, to define optimal follow-up strategies after ablation based on risk of recurrence, and potentially to target larger ablation margins for high risk patients. The fact that subtype identification was performed on biopsy specimens also suggests that even surgical and radiation patients may benefit from biopsies to identify high risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have recently been reported after stereotactic body radiation therapy in the setting of MIP and SOL subtypes. (25) This work may be used to improve patient selection and stratification, to define optimal follow-up strategies after ablation based on risk of recurrence, and potentially to target larger ablation margins for high risk patients. The fact that subtype identification was performed on biopsy specimens also suggests that even surgical and radiation patients may benefit from biopsies to identify high risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] In a LACE-BIO study-related report, patients with micropapillary/solid predominant (but not acinar/papillary) adenocarcinomas obtained a diseasefree survival and specific disease-free survival but no overall survival benefit from adjuvant chemotherapy. 25,26 Leeman et al 28 reported that the outcomes after stereotactic body radiation therapy for early-stage (I-IIA) lung adenocarcinoma correlate highly with histological subtype, with micropapillary and solid tumors portending significantly higher rates of locoregional and metastatic progression. Whether adjuvant chemotherapy improves survival in patients with stage I lung cancer remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Whether or not the predominant histologic subtype of pulmonary adenocarcinoma evaluated in biopsy specimens carries the same prognostic and predictive significance as shown for tumour resections has yet to be proven. For stereotactic body radiotherapy of the lung there is some hint that the subtype determined from core biopsies is relevant for treatment response and failure patterns [21]. As even small percentages of micropapillary and solid patterns seem to have prognostic impact [22,23], the detection of any amount of these high-grade patterns in biopsy specimens should have prognostic relevance as well, but sampling error remains a major drawback especially in biopsies with small tumour volumes included [24].…”
Section: Relevance Of Histological Subtypes and Molecular Featuresmentioning
confidence: 99%